Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1159/000302708
|View full text |Cite
|
Sign up to set email alerts
|

Differential Hemodynamic Response to Repetitive Transcranial Magnetic Stimulation in Acute Stroke Patients with Cortical versus Subcortical Infarcts

Abstract: Objective: To assess the cerebral vasomotor response to ipsilesional repetitive transcranial magnetic stimulation (rTMS) on transcranial Doppler (TCD) in patients with recent ischemic stroke without carotid occlusive disease, and to compare this response in patients with cortical and subcortical infarcts. Methods: Consecutive patients with first-ever anterior circulation acute ischemic stroke (<3 days) and no extra- or intracranial arterial stenosis were prospectively recruited. Patients were divided into 2 gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 47 publications
0
7
1
Order By: Relevance
“…To sum up, the CBF of the injured side increased while the uninjured side decreased after high-frequency rTMS treatment, which increased the inhibition of the injured side to the contralesional hemisphere, so as to reach the goal of hemispheric rebalance. But this is inconsistent with Khaleel et al’s (2010) findings, who indicated that CBF velocity increased both in ipsilateral and contralateral in middle cerebral artery after high-frequency rTMS in acute ischemic stroke. The reasons for the difference may be as follows.…”
Section: Discussioncontrasting
confidence: 81%
“…To sum up, the CBF of the injured side increased while the uninjured side decreased after high-frequency rTMS treatment, which increased the inhibition of the injured side to the contralesional hemisphere, so as to reach the goal of hemispheric rebalance. But this is inconsistent with Khaleel et al’s (2010) findings, who indicated that CBF velocity increased both in ipsilateral and contralateral in middle cerebral artery after high-frequency rTMS in acute ischemic stroke. The reasons for the difference may be as follows.…”
Section: Discussioncontrasting
confidence: 81%
“…28,29 Furthermore, the hemodynamic response to brain stimulation differs between cortical and subcortical lesions with an increase in blood flow velocity after stimulation in subcortical stroke, while this was less prominent in cortical stroke. 57 We conclude that lack of change in neural plasticity in ipsilesional cortex could be the result of either a bias toward LTP and/or cortical damage produced by the stroke.…”
Section: Discussionmentioning
confidence: 83%
“…Patients with lesions that involve the cortex did not appear to respond to stimulation and demonstrated reduced improvement in motor activity compared to those with subcortical lesions only [80]. Furthermore, it has been shown that the hemodynamic responses to brain stimulation also appear different between cortical and subcortical lesions with velocity of blood flow significantly increased after stimulation in subcortical stroke, but was less prominent in cortical stroke [81]. Different stages of stroke recovery also appear to influence neuroplasticity processes, with a spontaneous upregulation in neuroplasticity emerging early after stroke [2,3,5].…”
Section: Biomarkers and Determinants Of Response To Tdcsmentioning
confidence: 99%